TRANSFORMATION PRODUCTS AND MICROBIOLOGICAL ACTIVITY OF ANTIBACTERIAL DRUGS ASSESSED IN ANIMAL MODELS - Ibragimova, N.А; Lyu , М.B.; Jumabayeva , S.M.; Karzhaubayeva , R.A.; Sabitov , А.N.; Adambekov , D. (Eurasian Journal of Applied Biotechnology, 2019)
Transformed drugs can exhibit a wide range of new toxicological effects compared to those of their original compounds. Conventional wastewater treatment technologies are only able to partially remove many pharmaceutical preparations and their metabolites from the environment, if at all, resulting in their accumulation in soils and agricultural products. These compounds can then enter the human body via the food chain, which contributes greater selection for resistance of microorganisms to these drugs. In this study, we investigated the biotransformation of ciprofloxacin, metronidazole, and adduct iodine in rats. The sensitivity of Staphylococcus aureus, Enterococcus faecalis, and Escherichia coli strains to the used drugs was then determined in vitro and in vivo in a mouse model of sepsis. Ciprofloxacin, metronidazole, and iodine adduct biotransformation products were all detected in the urine and feces of rats during the 7-day course of application. The highest concentrations of ciprofloxacin and metronidazole were found in the urine, whereas the highest concentration of iodides was detected in the feces. In vitro studies showed that all three strains were sensitive to the test drugs. Treatment of mice with metronidazole, ciprofloxacin, and iodine adduct caused positive dynamics of the septicopyemia course, but resulted in the development of resistance to metronidazole. These results highlight the necessity to include detection of biotransformed pharmaceutical preparations and their metabolites in open water sources as part of routine monitoring programs of the Republic of Kazakhstan.